In Vitro Assessment of Cytokine Expression Profile of MCF-7 Cells inResponse to hWJ-MSCs Secretome - Mirabdollahi, Mansoureh; Haghjooy Javanmard, Shaghayegh; Sadeghi-Aliabadi, Hojjat (Advanced pharmaceutical bulletin, 2019)
Purpose: Several attempts have been made to identify the mechanisms by which mesenchymalstem cells (MSCs)-derived secretome exert anti-tumor or tumorigenic effects, but still furtherinvestigations are needed to explore this subject. Thus, in this study we want to examine theexpression of different cytokines in secretome of hWJ-MSCs and their effects on cytokineexpression profile of the MCF-7 tumor cells.Methods: The hWJ-MSCs were isolated and characterized according to the International Societyfor Cellular Therapy criteria. Then, secretome of hWJ-MSCs was collected and freeze-dried, and20 mg/mL of the freeze-dried secretome was used to treat MCF-7 cancer cells for 48 hours.Afterwards, the expression levels of 12 cytokines including IL-1a, IL-1b, IL-2, IL-4, IL-6, IL-8,IL-10, IL-12, IL-17A, TNFα, IFNγ and GM-CSF in secretome of hWJ-MSCs alone as well as insupernatant of tumor cells before and after treatment with hWJ-MSCs secretome were evaluated.Results: Our results indicate that MCF-7 cells express significant amount of IL-6 and IL-8.Moreover, significant amounts of IL-1a, IL-1b, IL-8, IL-6 and GM-CSF were detected in secretomeof hWJ-MSCs. Furthermore, IL-1a, IL-2 and IL-4 were expressed significantly by MCF-7 cellsafter their treatment with hWJ-MSCs-derived secretome.Conclusion: According to our findings, the hWJ-MSCs derived secretome contains differentcytokines which can exert either anti-tumor or tumorigenic effects.